Alveolar soft part sarcoma in a young woman: A case report from Hong Kong - Max K.H. Yam, MBChBFRCR; Kenneth K.K. Chan, MBBS (Radiology Case Reports, 2022)
Alveolar soft part sarcoma (ASPS) is a rare, highly vascular, deep soft tissue mesenchymal malignancy that is classically seen in the lower extremities of young adults. We reported a case of a 32-year-old young Chinese woman in Hong Kong with a biopsy-proven alveolar soft part sarcoma. The condition can be suggested by classical features using contrast-enhanced CT scans and MRIs or confirmed by image-guided biopsies. Early recognition of the condition is important due to its poor prognosis and lack of awareness. The mainstay of treatment for ASPS is complete surgical resection of the primary tumor and radiotherapy for microscopic residual disease at the primary site, or chemotherapy in special cases.